(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The effectiveness of managerial activity, which is measured by the ratio of results obtained to resources expended, is closely related not only to the professionalism of the manager, but also to his moral and ethical qualities. One of the key virtues that determines the quality of management is integrity. The purpose of the study is to characterize the content of the integrity of a sports manager and its impact on the effectiveness of professional activity. To achieve the goal of the study, a set of interrelated research methods was used, namely: analysis, synthesis and generalization of scientific information on the research problem, educational and methodological literature and Internet sources. Managerial integrity is a set of ethical qualities, such as honesty, fairness, openness, consistency, responsibility, which are manifested in the behavior of a person, transparency in decision-making, prevention of abuse of power and fairness in treating people. The results of the study proved that the integrity of a sports manager involves an impact on the effectiveness of management, which is manifested in the formation of trust in him, strengthening the authority of the manager (leader formation), creating a positive moral climate (motivating employees, reducing conflict, increasing responsibility and discipline) and improving management decisions. A sports manager plays a crucial role in ensuring the integrity of competitions, effective management of sports organizations, as well as educating the younger generation of athletes in the spirit of justice and respect. Integrity in sports management, along with managerial activities, ensures the formation of values that reflect democratic principles in the field of physical culture and sports. The results of the study indicate that integrity in sports management is not only a moral virtue, but also a critically important factor in effective management. It contributes to the formation of trust, support for the team, improving the moral climate and making effective, fair decisions. In today’s world, leaders without integrity lose not only respect, but also the opportunity to be truly effective.